A categorization of quality management and supply chain management frameworks - Assadej Vanichchinchai (Cogent Business & Management, 2019)
This article aims to comprehensively review, discuss, compare, contrast and categorize supply chain management (SCM) and quality management (QM) frameworks. SCM and QM literature were reviewed extensively. Their concepts and frameworks were discussed, compared, contrasted and classified. Several commonly accepted frameworks were raised for illustration. It was found that SCM and QM frameworks can be determined by generality (specific or generic) and scope (narrow or wide) into four categories, namely Qualifier, Improver, Extender and Winner. SCM and QM concepts and frameworks have similar evolutional trends. Understanding SCM and QM frameworks with their characteristics can help managers improve implementation success and returns. SCM evolution and promotion may be learned from those of QM as its counterpart.
Keywords: 650; supply chain management; quality management; framework; model; categorization